BERBEKAL AMALAN DALAM TARIKAT SUFI MENGHASILKAN BANYAK KARAMAH - Syamruddin Nasution (An-Nida', 2018)
The journals published in the practice of Sufi tributes produce many of these karamahs, which are answered free from the fortune of those who studied Sufi weaving experts to get forty karama included in the Sairu al-Salikin Li Babi Ihya'ulumuddin Book published by Shaykh Abdurrahman al-Kalantani who commented the book of Ihya al-'Ulumuddin by Imam al-Ghozali in volume three of the tenth chapter and the closing chapter. The rest is told beforehand that they too love wealth and charity donors, love the splendor of life, love to show off wealth, arrogant and endless, fortunately lucky people who are not deluded by the temptations of world life; they are the ones who change the Sufi tariqat who get forty lectures from Allah Ta'ala, twenty in the world and twenty in the hereafter. How to calculate the deeds done by Sufi experts who produce a lot of karamah. Sources of data in this study are library sources, data collection steps, ranging from data collection or collection, data verification, data interpretation and finally obtained. In analyzing the truth, the study tested using the cross check method. The results showed that many people were deluded into world life; will live wretched in the world and the hereafter otherwise people who are not trapped in world life and practice charity twenty in the world and twenty in the hereafter. Furthermore, also believe in arrogant drugs and enjoy showing off wealth by examining yourself what is boasted about, because this is material that comes from the soil and will be returned to the soil filled with dirt in every hole in the limbs and whatever we have eaten the rest of other people's parts and will stay for someone else.